Pengaruh Kualitas Pelayanan terhadap Kepuasan Masyarakat pada Dinas Perikanan Kabupaten Mukomuko - Aprianty, Henny; Marlenni, Desmi; Sakti, Budiman; Purnawan, Heru; Dani, Rahiman (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka Palembang, 2023)
This research was conducted at the Mukomuko Fisheries Service. The purpose of this research is to know the impact of reliability, responsiveness, safety, empathy, and concreteness on the satisfaction of the person being treated. This research was conducted using quantitative research where the main source of information was the people selected as respondents. Respondents were selected using a purposive sampling technique. Up to 75 people were interviewed using a non-probability-based sampling technique. Researchers used the main survey instrument (questionnaire) to collect data. Each question in the questionnaire contains 5 answer choices, each answer choice is evaluated according to a Likert scale. The data used in this study are quantitative analysis data supported by descriptive analysis (explanation). Quantitative analysis tool with multiple linear regression. While the hypothesis was tested using the t-test (t-test) and F-test (F-test) with a confidence level of 95 n alpha = 0.05. The results of the data analysis carried out show that the quality of service in terms of reliability, responsibility, security, empathy, and concrete influences the satisfaction of the people who work at the Kupaten Mukomuko Fisheries Service. The results of linear regression analysis often show that increasing reliability, responsiveness, security, empathy, and concreteness can increase service user satisfaction. The results of testing the hypothesis with the t-test give the calculated t values of the three variables studied > significance of t table < 0 > F table. Reliability, responsiveness, safety, empathy, and concreteness partially and at the same time have a significant effect on the satisfaction of the people who work in the Mukomuko fisheries service. Keywords: Service Quality, Community Satisfaction